2017
DOI: 10.1016/j.smim.2017.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage phenotype in response to ECM bioscaffolds

Abstract: Macrophage presence and phenotype are critical determinants of the healing response following injury. Downregulation of the pro-inflammatory macrophage phenotype has been associated with the therapeutic use of bioscaffolds composed of extracellular matrix (ECM), but phenotypic characterization of macrophages has typically been limited to small number of non-specific cell surface markers or expressed proteins. The present study determined the response of both primary murine bone marrow derived macrophages (BMDM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(90 citation statements)
references
References 80 publications
2
87
0
Order By: Relevance
“…80,81 Sicari et al have shown that degradation products of ECM bioscaffolds can directly activate macrophages toward a iNOS -/Fizz1 + macrophage phenotype. 25 Furthermore, Huleihel et al 82 conducted an exhaustive analysis of macrophage phenotype following exposure to ECM degradation products showing that ECM is consistently associated with downregulation of pro-inflammatory genes and proteins. The ability of ECM bioscaffolds to activate macrophages is well established.…”
Section: The Development Of ''Inert Biomaterials''mentioning
confidence: 99%
“…80,81 Sicari et al have shown that degradation products of ECM bioscaffolds can directly activate macrophages toward a iNOS -/Fizz1 + macrophage phenotype. 25 Furthermore, Huleihel et al 82 conducted an exhaustive analysis of macrophage phenotype following exposure to ECM degradation products showing that ECM is consistently associated with downregulation of pro-inflammatory genes and proteins. The ability of ECM bioscaffolds to activate macrophages is well established.…”
Section: The Development Of ''Inert Biomaterials''mentioning
confidence: 99%
“…In recent studies, some authors showed decellularized scaffolds polarize the macrophage response in vivo toward an M2 phenotype, an alternative pathway activation of macrophages [24, 28, 29]. Future studies with M1/M2 phenotypes will investigate this finding in DHP and DPPt.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, a recent study comparing macrophage activation after exposure to dECM derived from different tissues, highlighted heterogeneity in macrophage response due to distinct ECM degradation products. In particular, the exposure to urinary bladder matrix or small intestinal submucosa ECM differently affected murine bone marrow-derived macrophages, generating distinct gene expression profiles of several commonly investigated macrophage surface and activation markers [ 27 ]. Scaffolds deriving from the same tissue may also behave differently; dECM from skeletal muscle, for example, has been shown to trigger macrophage polarization towards the M2 anti-inflammatory phenotype in an in vivo model of skeletal tissue injury [ 28 ], but other studies reported no impact of skeletal muscle-derived ECM on macrophage plasticity [ 10 ].…”
Section: Immunomodulation By Implanted Scaffoldsmentioning
confidence: 99%